Etika Periklanan Indonesia Dari Segi Teori Kritis - Stefani Made Ayu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to discuss how the view of the practice of advertising in Indonesia is reviewed from a critical theory approach. When the cultural and media industries are only oriented to the commodity of the audience, only focusing on the economic value that is the trading process, the fact that ethics is only seen as the number one. In the end, there are advertisements that violate ethics, in order to get the attention of the audience and to sell their products to the market. The issue of the code of Ethics can be addressed when the code of advertising is well-socialized among advertising practitioners, especially agencies and communities. Especially for agencies, socialization needs to be implanted in order to avoid their ignorance in creating ads that are in the code of ethics.